Molecular Docking Studies of Active Phytochemicals from Leaf Extracts of Pseuderanthemum bicolor (SIMS) Radik with Alpha-amylase Inhibition Potential - Ramesh, B. S. (Cutting Edge Research in Biology Vol. 2, 2022)
Pseuderanthemum bicolor commonly called limang-sugat belonging to the family Acanthaceae. Leaves of P.bicolor were extracted with methanol, chloroform and ethyl acetate. The extracts were subjected for alpha-amylase inhibition assay and docking study using GC-MS analysis result. Leaf extracts were prepared by decoction method and have been evaluated for alpha-amylase inhibition assay and protein-ligand docking study against alpha-amylase protein. Among the three different extracts most significant enzyme inhibition was showed by ethyl acetate extract with highest inhibition of 43.1% at 1mg/ml concentration. The reference drug acarbose revealed 96% inhibition at 0.5mg/ml concentration. The major bioactive compounds obtained from methanol, chloroform and ethyl acetate extracts were 1,6;2,3-Dianhydro-4-Deoxy-Beta-D-Ribo-Hexopyranose, Pseduosarsasapogenin-5,20-Dien,Methyl Ether/ Hexatriacontane, Di-N-Decylsulfone/Octadecanal, Squalene respectively. A total of 19 secondary metabolites were tested for protein-ligand docking against alpha-amylase protein, with the reference drug acarbose demonstrating a binding energy of -7.8 Kcal/mol and forming 20 hydrogen bonds with the enzyme. Among the 19 test ligands, ‘2,2-Dibromocholestanone’from ethyl acetate extract exemplified highest binding energy of -9.3 Kcal/mol. The next highest remarkable inhibition was showed by ‘Pseduosarsasapogenin-5,20-Dien Methyl Ether’ present in the methanol extract, with a binding energy of -9.3 Kcal/mol with the formation of 2 hydrogen bonds. From the result it could be concluded that the P. bicolor contain effective bioactive compounds, needs further research on pharmacological aspects to develop a novel drugs.